Matching-Adjusted Indirect Comparison of Recombinant Factor IX Albumin Fusion Protein Versus Recombinant Factor IX Fc Fusion Protein for Weekly Prophylactic Treatment of Hemophilia B - Guillet, Benoit; Yan, Songkai; Hooper, Becky; Drelich, Douglass; Steenkamp, Jason; Tomic, Radovan; Mancuso, Maria Elisa (Advances in therapy, 2024)
Introduction Prophylactic treatment of hemophilia B with recombinant factor IX (rFIX) molecules with enhanced pharmacokinetics including rIX-FP (albutrepenonacog alfa; Idelvion © ) and rFIXFc (eftrenonacog alfa; Alprolix © ) have commonly been used in the clinic. In the absence of head-to-head comparative trials, the aim of this study was to estimate the efficacy of rIX-FP versus rFIXFc using matching-adjusted indirect comparisons (MAICs). Methods MAIC analyses leveraged individual patient data from the PROLONG-9FP trial and published summary-level data from the B-LONG trial for subjects who received weekly prophylaxis regimens. Individual patient data were used to assign weights and balance subjects from PROLONG-9FP with subjects from B-LONG on baseline disease severity, age, prior FIX regimen, and body mass index (BMI). Six efficacy outcomes were analyzed including annualized bleeding rate (ABR), annualized spontaneous bleeding rate (AsBR), annualized joint bleeding rate (AjBR), and the proportion of subjects without bleeding events (for total, spontaneous, and joint bleeding events). Results After adjustment for baseline disease severity, age, prior FIX regimen, and BMI, rIX-FP was associated with a statistically significant decrease in AsBR (rate ratio [RR] 0.42; 95% confidence interval [CI] 0.22, 0.82; P = 0.0107), and the proportion of patients without bleeding events (odds ratio [OR] 3.24; 95% CI 1.41, 7.45; P = 0.0057), spontaneous bleeding events (OR 3.47; 95% CI 1.56, 7.73; P = 0.0023), and joint bleeding events (OR 2.41; 95% CI 1.10, 5.26; P = 0.0274) compared with rFIXFc. Prophylactic treatment with rIX-FP was also associated with a numerically lower ABR (RR 0.75; 95% CI 0.32, 1.75; P = 0.5095) and AjBR (RR 0.82; 95% CI 0.37, 1.82; P = 0.6178). Conclusion The MAICs demonstrated that weekly prophylaxis treatment of severe hemophilia B with rIX-FP resulted in favorable efficacy outcomes as compared to rFIXFc. These findings suggest rIX-FP may offer improved clinical benefits over rFIXFc.